HUKUM WARIS ISLAM DAN PLURALISME HUKUM - Ernik, Ernik; Assaad, Andi Sukmawati; Kamal, Helmi (UIN Palopo, 2023)
Islamic Inheritance Law is a law that regulates the inheritance of the property of someone who has died given to the rightful, such as family and community who are more entitled or can be interpreted as a law that regulates the transfer of something from someone to someone else in the form of property and knowledge and honor. The provisions that have been outlined by Allah swt are listed in the Qur'an including Surah An-Nisa verse 7, 11, 12 with the existence of this inheritance law coupled with rules explaining the implementation of the Rasullah SAW, then all aspects of its implementation have legal rules. A person who is Muslim is strongly encouraged to divide the inheritance in accordance with what has been revealed in the Qur'an and guided by the Prophet in the hadith. The pluralism of inheritance law in Indonesia was influenced by the receptie theory during the Dutch era. Where until now inheritance law is still pluralistic, there are at least three legal systems that live and develop and are recognized, namely the Customary Law system, the Islamic Law system and the Western Law system. The significant difference that can be seen is that in the system of property distribution in customary law, it can be done before the owner of the property dies. Meanwhile, Islamic law and civil law require death in terms of the division of inheritance.